Emerging Materials & Technologies New approaches in Design Teaching Methods on four exemplified areas - Ferraro, Venere; Pasold, Anke (Design International - Open access, 2020)
The book focuses on four exemplified EM&Ts areas as results of the methods, gaps and issues related to their teaching methods. The four areas are: Experimental Wood-Based EM&Ts, Interactive Connected Smart (ICS) Materials Wearable-based, Carbon-based & Nanotech EM&Ts and Advanced Growing. It provides the setting up of a common/ novel method to teaching EM&Ts: to create new professional in young students, and to develop new guidelines and approach.